World Heritage Regionalism: UNESCO from Europe to Asia. Issue 4 (8th December 2015) - Meskell, Lynn; Liuzza, Claudia; Brown, Nicholas
Abstract: UNESCO World Heritage regions are historically constructed categories that do not easily map onto global geographies, yet they still continue to have important political and ethical implications in the international arena. Since their inception, regional categories have been at the heart of debates over global representation and equity in the World Heritage Committee. We include the recent controversy over uneven regional representation in elections to the Committee and the measures adopted to remedy this for the future. Specifically, the "Europe and North America" regional group has historically been the most dominant region and, as we demonstrate, continues to be so despite measures such as the Global Strategy. In the last decade, however, the "Asia and the Pacific" regional group has exhibited a growing presence in many aspects of World Heritage. We go on to examine overall trends from annual sessions of the World Heritage Committee from its start in 1977 to 2014 in terms of site inscription on the World Heritage List, membership on the Committee and size of national delegations in order to look in greater detail at the rising profile of Asia. This leads to a discussion of the different forms and understandings of regionalism, whether for Europe or Asia, and how some Asian delegations see their increased role and visibility in World Heritage.